PLURALISM AND SOCIAL JUSTICE IN PANCASILA DEMOCRACY: BETWEEN IDEALS AND REALITY: MENGGAPAI KEADILAN SOSIAL BERDASARKAN DEMOKRASI PANCASILA: ANTARA CITA-CITA DAN REALITAS - Damaitu, Emanuel Raja (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2025)
The Reform Era, which began with the fall of the Suharto regime in 1998, marked a shift towards a democratic system of governance. This system is considered suitable for Indonesia’s highly pluralistic society. However, in practice, pluralism often serves merely as a rhetorical slogan to reinforce Indonesia’s national unity. The dominance of fundamentalist groups remains a significant challenge to democracy, as evidenced by various cases, including obstacles to the construction of places of worship, difficulties in civil registration for adherents of Indigenous beliefs, and the requirement for students practicing indigenous faiths to choose an officially recognized religion in the formal education system. Using a conceptual and descriptive approach, this study examines the concept of social justice within Pancasila democracy and explores efforts to achieve it. The findings indicate that social justice in Pancasila democracy is reflected in fulfilling individuals' right to develop their potential and meet their basic needs. This aligns with the national development goals outlined in the Preamble of the 1945 Constitution, which aims to promote general welfare and advance national intelligence. Achieving social justice within Pancasila democracy requires collective awareness of the importance of coexistence in diversity. This awareness can be fostered through participatory development models that engage all societal sectors, ensuring that development is not solely the government's responsibility. From a legal perspective, the construction of laws must be oriented towards social integration within Indonesia’s plural society.